Cash, Card or Smartphone: The Neural Correlates of Payment Methods - Ceravolo, Maria Gabriella; Fabri, Mara; Fattobene, Lucrezia; Polonara, Gabriele; Raggetti, GianMario (Frontiers in Neuroscience, 2019)
Information technology innovations have pushed towards the digitalization of payments. We carried out an exploratory study to understand if and how brain activity can be modulated by the method of payment (cash, card and smartphone) or the amount of paid money (10€, 50€, 150€), or both. Sixteen healthy, right-handed, volunteers (8 females) underwent a fMRI session, during which 3 runs were presented with block-designed protocol. Each 5-min run was composed of a standard sequence of 12 videoclips, each lasting 12s and alternated with 12s-rest periods, displaying a human hand paying, each time, through a different method. When contrasting the BOLD signal change by payment method, a greater activation of the parietal cortex (BA40) and right insula (INS) was observed during the exposure of subjects to videoclips showing payments with cash than with either card or smartphone, with any amount of money. A significant greater activation of the right BA40 was observed with 150€ than 50€ and 10€, as well as of the right INS and posterior cingulate cortex with 150€ than with 10€, only in the cash condition. This pilot study indicates that cash enhances the salience and negative affective valence of parting with money, as suggested by the greater activity of areas processing the perceived utility of motor behavior (e.g. the parietal cortex), and the individual emotional involvement (e.g. INS). By highlighting that cash payment could represent a stronger self-regulating tool, these findings could be relevant for those interested in regulating compulsive shopping or digital gambling.